Shifting sands: Changes in community perceptions of mining in Ghana - Lawson, E.T.; Bentil, G. (Environment, Development and Sustainability, 2014)
The contribution of mining to the Ghanaian economy has been substantial. The mining sector is currently a major foreign exchange earner and contributes to long-term capital formation and fiscal payment to the state. However, the industry continues to have adverse consequences on the lives of local community dwellers, most of whom are often unprepared to deal with these impacts. Often, new mining exploration takes place on land that provides land-based livelihood to many rural people. Ironically, compensation payments seem to worsen poverty in the mining communities and bring about the social conflicts. Hence, whilst communities are highly welcoming of mining companies during exploration, they become resentful during operation of the mine. Using two communities in the Asutifi District of Ghana as case studies, this paper presents a candid assessment of the changes that occur in respondents' perception of mining during, before and after the inception of mining. It also examines the gender dimensions of the impacts of mining activities as well as the communities' sources of information. Since public participation is an integral part of the environmental assessment process in Ghana, the paper concludes by recommending among others, precise channels of communication and dialogue before mining begins and during the operation of the mine, to increase awareness among community members. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Communication; Community perceptions; Corporate social responsibility; Ghana; Impacts; Mining; Mining